Alliterative revivals - Chism, Christine (Middle Ages series., 2002)
Alliterative Revivals is the first full-length study of the sophisticated historical consciousness of late medieval alliterative romance. Drawing from historicism, feminism, performance studies, and postcolonial theory, Christine Chism argues that these poems animate British history by reviving and acknowledging potentially threatening figures from the medieval past-pagan judges, primeval giants, Greek knights, Jewish forefathers, Egyptian sorcerers, and dead ancestors. In addressing the ways alliterative poems centralize history-the dangerous but profitable commerce of the present with the past-Chism's book shifts the emphasis from the philological questions that have preoccupied studies of alliterative romance and offers a new argument about the uses of alliterative poetry, how it appealed to its original producers and audiences, and why it deserves attention now. Alliterative Revivals examines eight poems: St. Erkenwald, Sir Gawain and the Green Knight, The Wars of Alexander, The Siege of Jerusalem, the alliterative Morte Arthure, De Tribus Regibus Mortuis, The Awntyrs off Arthure, and Somer Sunday. Chism both historicizes these texts and argues that they are themselves obsessed with history, dramatizing encounters between the ancient past and the medieval present as a way for fourteenth-century contemporaries to examine and rethink a range of ideologies. These poems project contemporary conflicts into vivid, vast, and spectacular historical theaters in order to reimagine the complex relations between monarchy and nobility, ecclesiastical authority and lay piety, courtly and provincial culture, western Christendom and its easterly others, and the living and their dead progenitors. In this, alliterative romance joins hands with other late fourteenth-century literary texts that make trouble at the borders of aristocratic culture.